Coping and psychopathology in children with malignancy and bronchiectasis - PERDAHLI FİŞ, NEŞE; GÖKDEMİR, YASEMİN (WILEY, 2020)
Aim: We aimed to evaluate the coping styles and social support perceived by the children with two different chronic diseases (cancer and bronchiectasis), their mothers' coping styles and compare them with a control group without any chronic physical or psychiatric disorder. Methods: Our sample consisted of 114 children and adolescents, with an age range from 9 to 15 years. The data were collected by using schedule for affective disorders and schizophrenia for school-age children-present and lifetime version, kid-coping orientation to problems experienced (Kid-COPE), social support appraisals scale (SSAS), and COPE. Results: All three groups were similar with respect to age and sex distribution. Around 50% to 60% of the children in both patient groups had a psychiatric diagnosis. Remarkably, 30% of the children had an internalizing disorder. The most commonly used coping style by the mothers was religious coping in all groups. Kid-COPE scores did not significantly differ between groups. The scores on Family and Friend subscales of SSAS in the bronchiectasis group were significantly lower when compared with those of participants in hematology-oncology and control groups. Conclusion: Chronic medical illnesses may have a similar psychological impact on children regardless of disease-specific clinical presentations and outcomes. Future studies need to focus on identifying protective and risk factors that potentially mediate psychosocial well-being.
Keywords: chronic disease; coping; psychopathology; DEPRESSIVE SYMPTOMS; CANCER; PARENTS; ADOLESCENTS; ANXIETY; ADJUSTMENT; DISORDERS; DISTRESS; ILLNESS; DISEASE